2004
DOI: 10.1073/pnas.0401927101
|View full text |Cite
|
Sign up to set email alerts
|

TorI, a response regulator inhibitor of phage origin inEscherichia coli

Abstract: The torI gene has been identified by using a genetic multicopy approach as a negative regulator of the torCAD operon that encodes the trimethylamine N-oxide reductase respiratory system in Escherichia coli. The negative effect was due to a previously unidentified small ORF (66 aa) of phage origin that we called torI for Tor inhibition. Overexpression of torI led to an 8-fold decrease of the torCAD operon transcription. This operon is positively regulated, in the presence of trimethylamine N-oxide, by a fourste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Protein Purifications-IHF and TorI proteins were overproduced and purified as described (23,29). IntS was produced from C41(DE3) harboring plasmid pETintS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein Purifications-IHF and TorI proteins were overproduced and purified as described (23,29). IntS was produced from C41(DE3) harboring plasmid pETintS.…”
Section: Methodsmentioning
confidence: 99%
“…1). The torI gene is the last gene of the KplE1 prophage genome, originally identified using a genetic multicopy approach as a negative regulator of the torCAD operon that encodes the trimethylamine oxide reductase respiratory system in E. coli (23,24). The negative effect was due to a previously unidentified small open reading frame (66 amino acids) that we called torI for Tor inhibition.…”
mentioning
confidence: 99%
“…Immunoprecipitation-The E. coli ⌬ 3 strain harboring the pGPJ-His plasmid (30) was transformed with pBTorI (15). Cells were grown until A 600 reached 0.5 unit.…”
Section: Volume 286 • Number 45 • November 11 2011mentioning
confidence: 99%
“…The torI gene is the last gene of the KplE1 prophage genome and was originally identified using a genetic multicopy approach as a negative regulator of the torCAD operon that encodes the trimethylamine-oxide reductase respiratory system in E. coli (15). Despite its role as an inhibitor of the TorR response regulator, later work has shown that TorI is in fact a bona fide RDF for KplE1 phage excision (10).…”
mentioning
confidence: 99%
“…Some RDFs, such as Cox proteins of phages P2 and HP1, have additional regulatory functions outside recombination (9). TorI itself was originally identified as a negative response regulator of the TorR protein, which activates transcription of the torCAD operon, encoding the trimethylamine-N-oxide reductase respiratory system (10).…”
mentioning
confidence: 99%